2003
DOI: 10.1016/s1631-0691(03)00049-0
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in salt marshes: from patrimonial value to ecosystem functioning. The case study of the Mont-Saint-Michel bay

Abstract: Until 1979, European salt marshes were known only through the inventories of fauna and especially of flora. On such criteria, the salt marshes of the Mont-Saint-Michel bay (France) were regarded as most significant of the French coasts. However, it took 20 years of research on the role of these wetlands of the estuaries-salt marsh systems to highlight the ecological, social and economic interest of this ecotone, between continental and marine systems, a long time considered as territory "without value", except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 25 publications
(23 reference statements)
2
48
0
5
Order By: Relevance
“…The intertidal area covers 220 km 2 and contains 180 km 2 of mud and sand flats and 40 km 2 of salt marshes. Salt marshes are drained by a dense creek system (Lefeuvre et al, 2000) and are flooded during 43% of tides when the tidal range is greater than 11.25 m. Flooding lasts on average 2 h per tide. The rest of the time the salt marsh, including tidal creeks and vegetated tidal flats, is emerged.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations
“…The intertidal area covers 220 km 2 and contains 180 km 2 of mud and sand flats and 40 km 2 of salt marshes. Salt marshes are drained by a dense creek system (Lefeuvre et al, 2000) and are flooded during 43% of tides when the tidal range is greater than 11.25 m. Flooding lasts on average 2 h per tide. The rest of the time the salt marsh, including tidal creeks and vegetated tidal flats, is emerged.…”
Section: Study Sitementioning
confidence: 99%
“…Salt marshes are complex ecotones between terrestrial and marine systems and are among the most productive systems of the biosphere (Lefeuvre et al, 2000). Since the introduction of the outwelling concept (Odum, 1968), which states that tidal events export detrital organic matter produced in salt marshes to marine waters, strong evidence has also indicated that the export of organic matter from terrestrial to aquatic systems supports secondary production (Loneragan et al, 1997;Kurata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4). En anglais, cette zone est appelée pioneer zone ou pioneer marsh (Erchinger, 1985 ;Bouchard et al, 1998 ;Dijkema, 1998 ;van Rijn, 1998 ;Lefeuvre et al, 2000). Lefeuvre (2000) a utilisé l'expression « zone pionnière » à la place de haute slikke et a reconnu l'existence de trois niveaux dans le schorre : infé-rieur, moyen et supérieur, ce qui correspond à la réalité chez nous pour les schorres naturels les plus étendus.…”
Section: Terminologieunclassified